Integrated nutrient management in pearl millet (Pennisetum glaucum)-wheat (Triticum aestivum) cropping system - Kumar, Pawan; Nanwal, R K; Yadav, S K (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted in pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz.]-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system during 2002-03 and 2003-04 at Hisar, Haryana, consisting of 12 treatments laid out in randomized block design to evaluate the integrated nutrient management treatments in pearl millet wheat cropping system in sandy loam soils. The pooled grain yield of pearl millet was highest (3.31 tonnes/ha) with application of 100% recommended dose of NPK in both crops. In wheat highest pooled grain yield was recorded with 100% recommended dose of NPK in both crops (4.75 tonnes/ha) at par with 50% NPK + 50% N (farmyard manure) to pearl millet and 100% NPK to wheat (4.65 tonnes/ha) and significantly superior over the rest of treatments. Highest system grain yield (8.07 tonnes/ha) of both pearl millet and wheat was obtained with the application of 100% recommended dose of NPK in both crops. This may however be supplied either entirely through inorganic fertilizers or 50% recommended dose of NPK + 50% N through farmyard manure to pearl millet.